Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part VI.-Writing And Printing Papers from Paper Mulberry (Broussonetia papyrifera ) - Bhat, R. V.; Guha, s. R. D. (Indian Forester, 1952)
Experiments conducted in Madras State and Travancore-Cochin State indicate that paper mulberry (Broussonetia papyrifera, Vent.) can be easily raised in plantations from seeds. The species reproduces itself naturally and is a fast grower and a good coppicer. The bast fibre is used in Japan for the preparation of extremely strong and high quality papers. Laboratory experiments as well as pilot plant trials carried out in this Branch indicated that the wood of this species is a useful raw material for the production of writing and printing papers. Since the chemical pulp from this wood is short-fibred, an addition of about 25% of long-fibred pulp such as bamboo pulp in the furnish improves the strength properties of the paper.